2015
DOI: 10.1093/femspd/ftv022
|View full text |Cite
|
Sign up to set email alerts
|

F protein increases CD4+CD25+ T cell population in patients with chronic hepatitis C

Abstract: HCV is a global health problem with an estimated 230 million chronically infected people worldwide. It has been reported that a 17-kd protein translated from core-encoding genomic region can contribute to immune-mediated mechanisms associated with the development of the chronic disease. Also, Treg cells can be contributed to an inadequate response against the viruses, leading to chronic infection. Here we evaluated the ability of protein F to modulate the frequency of CD4+CD25+FoxP3+T and IL-10+T cells in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Several virus proteins are recognized to have ability to affect signal transduction in immune cells thus influencing effector functions of both innate and adaptive immunity [4][5]. Additionally, chronic activation of immune cells results in exhaustion of immune response [6] and activation of a subgroup of regulatory T cells [7] that contributes to the functional impairment of the virusspecific T cell response. Permanent presence of virus and sustained immune response results in prolonged inflammation and consequential liver injury.…”
Section: Introductionmentioning
confidence: 99%
“…Several virus proteins are recognized to have ability to affect signal transduction in immune cells thus influencing effector functions of both innate and adaptive immunity [4][5]. Additionally, chronic activation of immune cells results in exhaustion of immune response [6] and activation of a subgroup of regulatory T cells [7] that contributes to the functional impairment of the virusspecific T cell response. Permanent presence of virus and sustained immune response results in prolonged inflammation and consequential liver injury.…”
Section: Introductionmentioning
confidence: 99%
“…The first 10 amino acids of the core+1 protein play a stabilizing role in the conformational structure of the core+1 protein, leading to better folding, rather than acting as an antigenic region (5). Therefore, this homology does not interfere with the anticore+1 positive response (5); besides, the authors' previous study showed no cross-reactivity between the Abs against core+1, truncated core+1, and core proteins (10).…”
Section: Discussionmentioning
confidence: 95%
“…There are some reports indicating that chronic hepatitis C (CHC) infection is strongly associated with hepatocellular carcinoma (HCC) (3)(4)(5)(6)(7)(8)(9). There is neither effective vaccine for immunization, nor a broadly effective treatment for HCV infection (3).Among different factors associated with chronic HCV infection, alternate reading frame protein (ARFP) or core+1 protein is one the newest ones that can promote persistent infection (10)(11)(12). This protein is produced by a frame shift at codon 11 by a minority of ribosomes that initiate translation at the HCV AUG initiator codon of HCV genome (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in chronic HCV patients, 82% were positive for anti-F antibodies, showing a significant difference from the healthy individuals 5 . This protein increases the frequency of CD4+CD25+ Treg cells, which may be associated with persistent and chronic infection through subversion of the host immune response 6 F proteins could also enhance liver cell proliferation 7 , which is subsequently associated with the disease progression towards cirrhosis 8 . The protease function of HCV NS3 protein is also a crucial factor for the induction of liver fibrosis via interaction with cellular miRNAs and down-regulation of miRNA gene expressions 9,10 .…”
Section: Introductionmentioning
confidence: 99%